2017
DOI: 10.19173/irrodl.v18i1.2656
|View full text |Cite
|
Sign up to set email alerts
|

Enriching Higher Education with Social Media: Development and Evaluation of a Social Media Toolkit

Abstract: While ubiquitous in everyday use, in reality, social media usage within higher education teaching has expanded quite slowly. Analysis of social media usage of students and instructors for teaching, learning, and research purposes across four countries (Russia, Turkey, Germany, and Switzerland) showed that many higher education instructors actively use social media for private purposes.However, although they understand that their students also use it for learning purposes, and instructors sense the potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 31 publications
0
26
0
2
Order By: Relevance
“…In response, an openly accessible trilingual social media toolkit was developed which analyzes the teaching scenario with several questions, before suggesting, based on an algorithm, the best matching class of social media, complete with advice on how to use it for teaching purposes. This study explains the rationale behind the toolkit, its development process, and examines instructors' perceptions towards it [8]. f. Shen et al, study (2017) Educational practitioners have adopted social media to their online or mobile communities, little attention has been paid to investigate the social media messages related to online or mobile learning.…”
Section: Related Study a Feldman Study (2015)mentioning
confidence: 99%
See 2 more Smart Citations
“…In response, an openly accessible trilingual social media toolkit was developed which analyzes the teaching scenario with several questions, before suggesting, based on an algorithm, the best matching class of social media, complete with advice on how to use it for teaching purposes. This study explains the rationale behind the toolkit, its development process, and examines instructors' perceptions towards it [8]. f. Shen et al, study (2017) Educational practitioners have adopted social media to their online or mobile communities, little attention has been paid to investigate the social media messages related to online or mobile learning.…”
Section: Related Study a Feldman Study (2015)mentioning
confidence: 99%
“…Barriers are related to the skills and needs of teachers, whereas potential is more applicable for learners. Therefore, it can be said that solutions should be provided to support teachers overcoming possible barriers to effective social media integration in higher and continuing education [8]. However in spite of these barriers Through social online interaction and discussion adult learners collaboratively share messages not only relating to their tasks and concerns that they may have about that task, but also their own strategies on how a specific task can be solved and completed.…”
Section: Challenges Of Social Mediamentioning
confidence: 99%
See 1 more Smart Citation
“…However, Gülbahar, Rapp, Kilis, and Sitnikova (2017) argued that social media and social networking applications cannot achieve educational purposes without a deliberate learning activity design. With a deliberate learning activity design, learners can achieve higher learning performance.…”
Section: Social Networking Enhanced Learningmentioning
confidence: 99%
“…For example, Mnkandla and Minnaar (2017) found that social media could adopt a conceptual framework for online collaborative learning (OCL) to facilitate deep learning and the creation of knowledge in e-learning at higher educational institutions. Gülbahar et al (2017) also found that providing instructors with a social media toolkit served as a guide to steer the students' discussions in the appropriate direction. Such social media toolkit provides instructors with guidance regarding the effective selection and integration of social media into their courses.…”
Section: Social Networking Enhanced Learningmentioning
confidence: 99%